Aesthetic rehabilitation of diastema using the direct technique with composite resin: Case report (Research, Society and Development, 2021)
Objective: The objective of this paper is to report the clinical case of esthetic rehabilitation of diastemas, with 3D diagnostic wax-up, use of a palatal guide and closure of dental spaces with composite resin. Methodology: Based on the patient's permission through the Free and Informed Consent Term to share their image for the proper purpose, this study is a clinical case report of descriptive analytical nature (Pereira et al., 2018). Case Report: Female patient, 23 years old, attended the Dental Clinic of Centro Universitário FAMETRO, with the main complaint “Dissatisfaction due to the space between the anterior teeth and disproportionate sizes”. During anamnesis, no health problems or systemic changes were reported. Final Considerations: In this way, carefully oriented to the restorative protocol, the success of the technique used and the final result was achieved, bearing in mind the clinical aesthetic concepts and the patient's expectations.